Pengaruh Applied Behaviour Analisys Terhadap Kemampuan Berbahasa Anak Autis - Rohmah, Hamdiyatur; ., M Farid (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2016)
The objectives of the study are to investigate the effect of Applied BehaviorAnalysis method on autistic children’s language development skill and to help parents tocoach their children in order to communicate better. The research uses some theories onlanguage development in American Academy of Pediatrics; Evaluation and Management oflanguage and Speech Disorders (2005), Speech and Language Milestone (2006), and ChildDevelopment, Santrock (2007). The subject of the study, are 4 autistic children as theexperiment group with the mothers in an intervention program with languagedevelopment’s module which is assisted by psychologist and a linguist. Data sample istaken by purposive sampling technique (subject group study based on study objective) withone experiment group only. Analysis is used to see the result of before and after treatment.The result of paired sample analysis shows t = - 4,753 p = 0,018 (P < 0,05). It means thereis a significant increase on language development of the autistic children.Keywords : Applied Behavior Analysis, Children with Autism, Child Development, LanguageDevelopment.